Prediction of lifetime of data storage on optical disks - Petrov, V. V.; Kryuchyn, A. A.; Berezin, B. A.; Beliak, I. V.; Shyhovets, O. V. (Інститут проблем реєстрації інформації НАН України, 2016)
The results of analysis of usage of accelerated guaranteed information lifetime estimation methods are presented. Particular attention is paid to testing of media for long-term storage of information. The main causes of a significant difference in terms of data storage on compact discs during accelerated testing have been determined. Fig.: 9. Refs: 37 titles.